PENGARUH FREKUENSI PAPARAN STRESOR CAHAYA SAAT KEBUNTINGAN TERHADAP JUMLAH DAN INDEKS APOPTOSIS SEL NEURON OTAK MENCIT (Mus musculus) BARU LAHIR - RACHMAT WILLY, NIM011314653004 (2017)
The main purpose of this experimental study was to compare the apoptotic index and number of the offspring’s Mus musculus brain neurons between intervention and nonintervention group to physical (light) induced stress during pregnancy. Experimental study, double blind randomized controlled study. Intervention groups were given 300 – 400 lux light once and twice daily with 45 minutes for each exposure, in the morning (for 1 time exposure) and both morning and night (for 2 times exposure) at the same time during early pregnancy until 2 days before delivering the fetus. After delivery, for all groups, the offspring sacrificed by decapitation and brain neuron cells were prepared by double staining with HE and TUNEL method to calculate apoptotic index and number of brain neurons. The study conducted at Veterinary Faculty of Airlangga University Surabaya after ethical clearance. Laboratory staining was done by Veterinary Faculty of Airlangga University Surabaya. It was found that number of brain neurons (3,2 ± 1,55) in intervention group (P2) compare with (10,3 ± 3,37) in control group (K0), and apoptotic index (3,64 ± 1,38) in intervention group (P2) compare with (1,46 ± 1,03) in control group (K0). According to statistic test the different were significant with p = 0.000 both of those group. The apoptotic index of the intervention group was significantly higher than non intervention (control) group and the number of brain neurons of the intervention group was significantly less than non intervention group (control).